2023
DOI: 10.3892/ijmm.2023.5239
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reverses oxidative stress‑induced mitochondrial dysfunction in pre‑osteoblasts via the EGFR/GSK‑3β/calcium pathway

Abstract: Oxidative stress is one of the main causes of osteoblast apoptosis induced by post-menopausal osteoporosis. The authors previously found that metformin can reverse the loss of bone mass in post-menopausal osteoporosis. The present study aimed to further clarify the effects and mechanisms of action of metformin in post-menopausal osteoporosis under conditions of oxidative stress. Combined with an in-depth investigation using the transcriptome database, the association between oxidative stress and mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Both in vivo and in vitro experimental investigations have delineated the pivotal role of GSK-3 activity in governing mitochondrial function within skeletal muscle cells. Specifically, studies involving GSK-3 knockout (KO) have demonstrated a reduction in mitochondrial oxidative damage coupled with an augmentation of mitochondrial biogenesis ( Wang et al, 2020 ; Cui et al, 2022 ; Cao et al, 2023 ). Its inactivation is usually caused by phosphorylation of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vivo and in vitro experimental investigations have delineated the pivotal role of GSK-3 activity in governing mitochondrial function within skeletal muscle cells. Specifically, studies involving GSK-3 knockout (KO) have demonstrated a reduction in mitochondrial oxidative damage coupled with an augmentation of mitochondrial biogenesis ( Wang et al, 2020 ; Cui et al, 2022 ; Cao et al, 2023 ). Its inactivation is usually caused by phosphorylation of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…It also protects the differentiation potential of osteoblastic stem cells in high glucose environment and activates the Nrf2/HO-1 signaling pathway to regulate the inhibition of osteogenic differentiation caused by high glucose; in addition, metformin can reverse the apoptosis caused by glucocorticoids through the action of AMPK/mTOR/p70S6K pathway on osteoblastic cells, thus playing a role in pharmacological osteoporosis. [23][24][25][26][27] More specific mechanisms are being investigated in further studies. Metformin, as a first-line glucose control agent, has certain limitations when used as an osteoporosis prevention and treatment agent.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vivo and in vitro experimental investigations have delineated the pivotal role of GSK-3 activity in governing mitochondrial function within skeletal muscle cells. Specifically, studies involving GSK-3 knockout (KO) have demonstrated a reduction in mitochondrial oxidative damage coupled with an augmentation of mitochondrial biogenesis (Wang et al, 2020;Cui et al, 2022;Cao et al, 2023). Its inactivation is usually caused by phosphorylation of substrates.…”
Section: Sqp Improves Lipid Metabolism Protects Mitochondrial Morphol...mentioning
confidence: 99%